PX- and FYVE-mediated interactions with membranes: simulation studies. - Psachoulia, E; Sansom, MS (2009)
Molecular dynamics simulations have been used to explore the interactions of two PI(3)P-binding domains with their PI ligands and with a phospholipid bilayer. Three simulations each of the EEA1-FYVE domain and the p40(phox)-PX domain have been compared: with the protein in an apo state, with a bound Ins(1,3)P(2) molecule, and bound to a PI(3)P molecule embedded in a lipid bilayer. Two main questions were addressed in analysis of the simulations: (i) the location of these domains relative to the lipid bilayer and (ii) their interactions with the lipids, both specific interactions via bound PI(3)P and nonspecific interactions with bilayer phospholipids. Both domains underwent a decrease in dynamic flexibility on binding to the ligand and to the membrane, this being more pronounced for the FYVE domain. Compared to their starting locations [docked to a membrane-inserted PI(3)P molecule], each of the domains penetrated more deeply into the lipid bilayer. For FYVE, nonspecific protein-lipid interactions were formed mainly by the N-terminal hydrophobic region of the protein. For PX, both the alpha1-alpha2 and the beta1-beta2 regions penetrated the bilayer. There appeared to be more marked dynamic fluctuations in hydrogen bonds between basic side chains and PI(3)P for FYVE than for PX, but for both domains, such interactions were maintained throughout the simulations. The simulations agree well with available biophysical data, suggesting this computational method may be used to predict protein-bilayer interactions for other PI-binding proteins.